Estrategias de marketing digital para el posicionamiento de marca en la empresa Makikum Constructora Inmobiliaria de la ciudad de Salcedo, provincia de Cotopaxi, año 2019” - Alvarado Garzón, Esteban Paul (2020)
The purpose of this research is to carry out a detailed analysis of the digital marketing strategies applied by the company Makikum Constructora Inmobiliaria S.A .; to demonstrate the empirical development in the management of digital media where the brand communicates. From this analysis, the lack of concordance in the contents generated in the digital media of the company is identified as the main fault, since, on the website there is no update of the information in relation to the contents generated in social networks , which is why the creation of a digital marketing plan is proposed with the development of content strategies to improve brand communication in digital media. Due to the empirical management of its digital brand communication, there is no dynamism within the company's external and internal communication and therefore the absence of an adequate interaction between client - company, thus obtaining a weak positioning in the digital media. With the execution of the marketing plan developed in this project, the quality of content published on the company's social networks has been improved, creating a continuous interactivity with users and keeping them updated with the progress of works and products offered by the company. Additionally, this research contributed to improve the internal communication of the construction company, thus improving customer service within the digital market and increasing brand positioning in it, providing organization in published content and optimizing the search time of social networks of the company and its information. Descriptive Terms: Digital marketing, digital content, brand